Resilience-based intervention for at-risk adolescents - Alwi, Azlin (2013)
The present study was carried out to test the effectiveness of a resilience-based intervention in improving at-risk adolescents’ perceived social support, life satisfaction and distress. A program named “Percaya Diri dan Cemerlang” (Believe in Oneself and Excel) was developed to increase resilience in adolescents. It was hypothesized that at-risk adolescents who participated in the program would report more social support, higher life satisfaction and lower distress than a control group who did not undergo the program. The intervention program was carried out for 90 minutes each week for 12 weeks. Thirty three at-risk adolescents were divided into two groups: the treatment group (n=16) and the control group (n=17). The two groups completed pre- and post-test scores on the three measures of support, life satisfaction, and distress. The study also collected qualitative data from the adolescents, their parents and class teachers after the intervention. Results showed that adolescents in the treatment group reported higher social support, but no difference was observed in their life satisfaction and distress scores. The qualitative results provided additional support, indicating the possible beneficial effects of such programs on at-risk adolescents.